Effects of the European Economic and Monetary Union (EMU) on Taxation and Interest Spending of National Governments - Mongelli, Francesco (IMF Working Papers; Working Paper ;, 1997)
This paper examines the interest spending and taxation channels through which EMU could affect the public finances. It provides a framework for examining different views on a further narrowing of interest rate differentials. A model of Blanchard and Fischer is amended to analyze the two channels, and empirical evidence on the tax harmonization process is presented. The paper argues that 'high-debt' and 'high-tax' countries pursuing prudent fiscal policies could benefit the most from EMU: if monetary and widespread fiscal discipline are jointly established, interest rates could decline rapidly, while tax harmonization is likely to be gradual.